TWO QUESTIONS, ONE ANSWER: UNAMBIGUOUS RATIONALITY. (March 2021) - Mueller, Andy
ABSTRACT: Timothy Williamson recently argued that the notion of epistemic rationality is ambiguous between a Content-oriented schema and a Disposition-oriented schema. I argue that the Disposition-oriented schema suggested by Williamson is not faithful to the main idea behind it and that it should be replaced with the Disposition-Manifestation schema. This replacement suffices for avoiding Williamson's ambiguity thesis.